COMPARATIVE CHARACTERISTICS OF LIFE QUALITY AND HEALTH CONDITION IN PATIENTS WITH INFILTRATIVE TUBERCULOSIS OF LUNGS IN DYNAMICS DURING DIFFERENT STAGES OF MEDICAL REHABILITATION - Tsapenko, Y.P.; Boiko, M.G.; Kraevska, O.O.; Alieva, N.M.; Krasnoshapka, Y.O. (World of Medicine and Biology, 2012)
Investigation is to study and carry out comparative analysis of life quality and health condition indices in dynamics in patients with firstly diagnosed infiltrative tuberculosis of lungs during in-patient (H) and out-patient (P) stages of rehabilitation. Life quality and health condition indices (QL) in researched groups were lower than in control group and are the following: 1-st (H) (83.76±0.53 points); 1-st (P) 2 (93.20±0.56 points). QL at the beginning of treatment in out-patient group is higher (93.20±0.56 points) compared with in¬patient group (83.79±0.53 points). QL improvement dynamics during medical rehabilitation is significantly higher in out-patient group: from 93,20±0,56 to 98,14±0,59 points; these indices almost correspond to QL indices of healthy persons of control group (99,28±0,18 points). Life quality of out¬patients with tuberculosis is markedly higher from the beginning of treatment and during its progress.